Juridical Review of Immigration Control at TPI Soekarno-Hatta: Comparison of Icao Literature, International Best Practice, and Immigration Office E-Office - Erlangga Eka Saputra; Lasbeth Parulian Lamsihar; Muhammad Bintang Anggriawan (LEGAL BRIEF, 2022)
The development of information and communication technology as well as the flow of globalization in this era has provided many conveniences related to transnational travel, in this case migration between countries is an interesting phenomenon. Because these migration flows can cause a threat to the security and defense of a country. With a research model that focuses on immigration checkpoints that include human variables, documents, country of origin, country of destination. These variables will be analyzed to obtain data containing weaknesses in the immigration cross-border inspection system followed by a formula to improve the cross-border inspection system at Indonesian immigration checkpoints. With the hope that safe and effective services will be achieved, followed by the disintegration of the nation and state. It is also necessary to pay attention to improving the cross-border inspection system at immigration checkpoints. Indonesia can see inspection standards abroad that have been proven safe and effective as a reference in improving immigration inspection services.